Ten years of external control of the fluoride level in public drinking water provided by Brazilian cities, Brazil, 1996-2006 - Jaime Aparecido Cury; Maria da Luz Rosário de Souza; Carolina de Oliveira; Regiane Cristina do Amaral; Danilo Bonadia Catani (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate the program of external control of water fluoridation performed in the periods between 1996 and 2006 by ten cities: eight in the State of São Paulo, one in Minas Gerais and another in the State of Ceará. Methods: The water samples were collected by the interested parties and sent to the Oral Biochemistry Laboratory of the Piracicaba School of Dentistry of the State University of Campinas, where they were analyzed with a fluoride ion-specific electrode. Results: Of the 3845 samples analyzed, 63.8% were in accordance with the values considered optimal (0.6 to 0.8 ppm F), with 19.7% of them presenting values below the minimum and 16.5%, above the maximum defined by Brazilian Standards. Furthermore, the majority of cities did not regularly maintain the program of external control of water fluoridation. Conclusion: Considering that approximately 40% of the water samples presented a fluoride ion concentration that did not comply with the Brazilian legislation, this study emphasizes the need for a regular program of sanitary vigilance of public water supply fluoridation.